Estimating the economic burden of cardiovascular events in patients receiving lipid-modifying therapy in the UK. Issue 8 (5th August 2016) - Danese, Mark D; Gleeson, Michelle; Kutikova, Lucie; Griffiths, Robert I; Azough, Ali; Khunti, Kamlesh; Seshasai, Sreenivasa Rao Kondapally; Ray, Kausik K
Abstract : Objectives: To characterise the costs to the UK National Health Service of cardiovascular (CV) events among individuals receiving lipid-modifying therapy. Design: Retrospective cohort study using Clinical Practice Research Datalink records from 2006 to 2012 to identify individuals with their first and second CV-related hospitalisations (first event and second event cohorts). Within-person differences were used to estimate CV-related outcomes. Setting: Patients in the UK who had their first CV event between January 2006 and March 2012. Participants: Patients ≥18 years who had a CV event and received at least 2 lipid-modifying therapy prescriptions within 180 days beforehand. Primary and secondary outcome measures: Direct medical costs (2014 £) were estimated in 3 periods: baseline (pre-event), acute (6 months afterwards) and long-term (subsequent 30 months). Primary outcomes included incremental costs, resource usage and total costs per period. Results: There were 24 093 patients in the first event cohort of whom 5274 were included in the second event cohort. The mean incremental acute CV event costs for the first event and second event cohorts were: coronary artery bypass graft/percutaneous transluminal coronary angioplasty (CABG/PTCA) £5635 and £5823, myocardial infarction £4275 and £4301, ischaemic stroke £3512 and £4572, heart failure £2444 and £3461, unstable angina £2179 and £2489 and transient ischaemic attack £1537 and £1814. The mean incremental long-term costs were: heart failure £848 and £2829, myocardial infarction £922 and £1385, ischaemic stroke £973 and £682, transient ischaemic attack £705 and £1692, unstable angina £328 and £677, and CABG/PTCA £−368 and £599. Hospitalisation accounted for 95% of acute and 61% of long-term incremental costs. Higher comorbidity was associated with higher long-term costs. Conclusions: Revascularisation and myocardial infarction were associated with the highest incremental costs following a CV event. On the basis of real-world data, the economic burden of CV events in the UK is substantial, particularly among those with greater comorbidity burden.